Image encryption scheme by combining the hyper-chaotic system with quantum coding. (January 2020) - Luo, Yuling; Tang, Shunbin; Liu, Junxiu; Cao, Lvchen; Qiu, Senhui
Highlights: A novel image encryption scheme is proposed based on hyper-chaotic system and quantum coding. A novel enhanced quantum representation (NEQR) model is applied to image processing. The bit-level adjacent-exchange operation is designed based on NEQR model. A novel image scrambling method based on quantum location coding is proposed. Experimental results demonstrate a good security performance. Abstract: The application of quantum mechanisms in image processing has attracted wide attention. In this paper, an image encryption scheme that is based on hyper-chaos and quantum coding is proposed. First, based on a novel enhanced quantum representation (NEQR), the bit-level adjacent-exchange operation is implemented to pre-process the plain-image, which has lower computational complexity compared to conventional bit-level switching operations. Then, the processed image is diffused by the quantified sequences where the self-adapting parameters are applied to quantify the sequences that are generated by Chen's hyper-chaotic system. In addition, inspired by the quantum coding structure, a novel scrambling method that is based on quantum location coding is proposed. This method is used to further scramble the diffused image to obtain the final cipher-image. The experimental results and performance analysis demonstrate that the proposed image encryption scheme has high security performance.